2021
DOI: 10.31235/osf.io/7hcwp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Public fear of protesters and support for protest policing: An experimental study

Abstract: As protests erupted across the United States in recent years over politically polarized issues (e.g., Black Lives Matter, COVID-19 restrictions), so too did questions about when and how police should respond. The context of these protests and how police reacted to them varied substantially, with limited understanding of relevant public attitudes. Public opinion is double-edged; it is critical for police legitimacy and influences criminal justice policy, but it also often reflects racial animus. We hypothesized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
(100 reference statements)
0
4
0
Order By: Relevance
“…Like crime trends in the UK and the USA ( Boman and Gallupe, 2020 ; Langton et al ., 2021 ), crime trends in Israel have also changed, including a significant rise in calls for service during lockdowns ( Bar-Tzvi, 2020 ). Finally, the IP were required to handle pandemic-related protests and demonstrations ( Shany, 2020 ), similar to those witnessed in the USA, UK, and Europe ( Metcalfe and Pickett, 2020 ). In sum, we consider Israel to be a useful setting for demonstrating what may happen to public attitudes towards the police over the COVID-19 period.…”
Section: Methodsmentioning
confidence: 99%
“…Like crime trends in the UK and the USA ( Boman and Gallupe, 2020 ; Langton et al ., 2021 ), crime trends in Israel have also changed, including a significant rise in calls for service during lockdowns ( Bar-Tzvi, 2020 ). Finally, the IP were required to handle pandemic-related protests and demonstrations ( Shany, 2020 ), similar to those witnessed in the USA, UK, and Europe ( Metcalfe and Pickett, 2020 ). In sum, we consider Israel to be a useful setting for demonstrating what may happen to public attitudes towards the police over the COVID-19 period.…”
Section: Methodsmentioning
confidence: 99%
“…Relatedly, in light of the social unrest of 2020 following the Floyd murder, scholars should develop new indicators of racialized attributions and attitudes (Chudy, 2021)—and test their influence on support for decriminalization policies, preferably using vignettes and experimental designs to manipulate conditions under which support might be tempered or amplified. In a recent experiment conducted a few months after the Floyd murder and subsequent public demonstrations, Metcalfe and Pickett (2021) found that racially resentful respondents were more in favor of repressive policing tactics to control protestors (e.g., shooting rubber bullets) in general, and especially likely to support repressive law enforcement action when the protests advanced the rights of racial and ethnic minorities. Racial resentment is generally associated with support for “get tough” laws, such as capital punishment (Peffley et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Given this scholarship, the operationalization of “post-2020” racialized attitudes and experiences (e.g., Metcalfe & Pickett, 2021) could include measuring the extent to which one recognizes racial inequities in the justice system, perceptions of the BLM movement and protestors (e.g., support, whether one participated in a protest), and other experiences (e.g., confronting someone using racist language). Such indicators may be associated with public willingness to support reforms aligned with addressing racial bias.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, I.P. officers were required to handle pandemic-related protests and demonstrations (Shany 2020a), similar to those in the United States, UK and Europe (Metcalfe and Pickett 2021). Thus, we consider the COVID-19 pandemic in Israel a useful setting for examining the questions at the heart of the present study.…”
Section: Methodsmentioning
confidence: 99%